LoRaWAN Link Layer - Seller , Olivier (Journal of ICT Standardization, 2021)
The LoRaWAN Link Layer specification [1] is a communication protocol for the Internet of Things. It targets low power, long range, low cost communication using unlicensed spectrum. Network topology is collaborative, which reduces a lot protocol signalling compared to a cellular network. The device is connected to a network server, and protocol overhead is limited to 13 bytes for any data frame. There are three classes of operation. Class A is optimized for low power operation of end-devices, while class B and class C offer reduced downlink latency. The protocol specification offers several mechanisms to adjust the link layer parameters: adaptive data rate, adaptive power control, variable repetition rate, and channel selection.